Determinant Analysis of Cultural Poverty in Kedu Raya Region - Jannah, Siti Nur; Wijaya, Riko Setya; Perdana, Putra (Gorontalo Development Review, 2026)
This study aims to analyze the determinants of cultural poverty in the Kedu Raya Region by examining the effects of Minimum District/City Wage, Life Expectancy, Average Years of Schooling, and Dependency Ratio on the number of poor people. Using panel data from six districts/cities in Kedu Raya from 2015 to 2024, the analysis was conducted through a log-linear panel regression model. The results show that the city minimum wage has a negative and significant effect on poverty levels, indicating that higher minimum wages help reduce poverty. Average Years of Schooling also has a negative and significant effect, emphasizing the crucial role of education in shaping economic behavior and reducing cultural poverty. In contrast, life expectancy and dependency ratio exhibit positive but insignificant effects. Simultaneously, all variables collectively influence poverty levels in the region. These findings highlight that improving education, enhancing health quality, and implementing appropriate wage policies can effectively reduce cultural poverty and support sustainable human development in the Kedu Raya Region.